1982
DOI: 10.1007/bf00441209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-content zinc and copper formula on infant nutrition

Abstract: The zinc (Zn) content of commercially available formula milks in Japan is less than that of breast milk obtained during the first three months of lactation, but is similar to that at five months of lactation. The copper (Cu) content of the formula milks is much lower than that of breast milk obtained during the five months. These two trace elements were measured in serum (at birth, one, three, and five months of age), hair (at birth and at five months of age) and urine (at one, three and five months of age) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
1

Year Published

1984
1984
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 22 publications
7
36
1
Order By: Relevance
“…Berfenstam (1952) reported very high serum levels in 20-26 week old fetuses and Sann et al (1980) found a significant negative correlation between serum Zn level and gestational age. These observations are comparable to our findings that the serum Zn level at birth was higher in the low birth weight infants than in the full term infants measured in our laboratory previously (Higashi et al 1982). The decline of serum Zn level during the first month of life found in the present study had been reported by many investigators (Gibson and Dewolfe 1981;Higashi et al 1982) and this was probably correlated well with negative Zn balance in the newborn period (Cavell and Widdowson 1964;Dauncey et al 1977).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Berfenstam (1952) reported very high serum levels in 20-26 week old fetuses and Sann et al (1980) found a significant negative correlation between serum Zn level and gestational age. These observations are comparable to our findings that the serum Zn level at birth was higher in the low birth weight infants than in the full term infants measured in our laboratory previously (Higashi et al 1982). The decline of serum Zn level during the first month of life found in the present study had been reported by many investigators (Gibson and Dewolfe 1981;Higashi et al 1982) and this was probably correlated well with negative Zn balance in the newborn period (Cavell and Widdowson 1964;Dauncey et al 1977).…”
Section: Discussionsupporting
confidence: 93%
“…These observations are comparable to our findings that the serum Zn level at birth was higher in the low birth weight infants than in the full term infants measured in our laboratory previously (Higashi et al 1982). The decline of serum Zn level during the first month of life found in the present study had been reported by many investigators (Gibson and Dewolfe 1981;Higashi et al 1982) and this was probably correlated well with negative Zn balance in the newborn period (Cavell and Widdowson 1964;Dauncey et al 1977). Cavell and Widdowson (1964) showed that breast fed full term infants aged 5 to 8 days were in negative Zn balance averaging -230 ,u g/kg/day.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations